2019
DOI: 10.3390/w11051096
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Drought Pattern Changes Due to Climate Variability: Case Study in Afghanistan

Abstract: We assessed the changes in meteorological drought severity and drought return periods during cropping seasons in Afghanistan for the period of 1901 to 2010. The droughts in the country were analyzed using the standardized precipitation evapotranspiration index (SPEI). Global Precipitation Climatology Center rainfall and Climate Research Unit temperature data both at 0.5° resolutions were used for this purpose. Seasonal drought return periods were estimated using the values of the SPEI fitted with the best dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 55 publications
1
77
0
Order By: Relevance
“…It has been reported that the frequency and severity of droughts have increased across the world in recent years. Therefore, assessment of the changes in droughts is crucial for the development of resilience to global environmental changes (Dabanlı et al, 2017;Güçlü, 2018;Şen, 2018;Qutbudin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the frequency and severity of droughts have increased across the world in recent years. Therefore, assessment of the changes in droughts is crucial for the development of resilience to global environmental changes (Dabanlı et al, 2017;Güçlü, 2018;Şen, 2018;Qutbudin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This area also experiences a broad range of variations in temperature. The mean temperature in July on the plains is of the range 0-8 • C with the absolute minimum temperature ranging from −20 to −25 • C. The mean temperatures in July on the plains range from 24 to 32 • C with a 45 • C absolute maximum temperature [30]. The climate of Afghanistan is subtropical and continental, in which summers are hot and sunny while winters are often cold and relatively rainy.…”
Section: Study Area and Datasetsmentioning
confidence: 99%
“…The mean temperature in July on the plains is of the range 0-8 °C with the absolute minimum temperature ranging from −20 to −25 °C. The mean temperatures in July on the plains range from 24 to 32 °C with a 45 °C absolute maximum temperature [30].…”
Section: Study Area and Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrological, climatological, and metrological analyses are mainly based on the availability of rainfall data [1], although problems associated with missing data are common and exist for various reasons. This may be the result of stations being relocated because of urbanization, errors in the methods implemented for measuring the rainfall amount, or the breakdown of instruments for a specific period, particularly in areas of flooding [2].…”
Section: Introductionmentioning
confidence: 99%